Students' Perceptions on Ice Breaking Techniques in the SchriftlicherAusdruck Course - Wahyuningsih, Fahmi; Parnaningroem, Raden Roro Dyah Woroharsi; Pujosusanto, Ari; Widyastuti, Widyastuti; Az Zahro', Dzakiyyah Fathimah (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2024)
The purpose of this research was to determine students' perceptions of the applying of ice breaking in learning German language, particularly in the Schriflicher Ausdruck course in Unesa's German language education major. This course is often taught teacher-centre, causing students get bored. Ice breaking technique might lessen the boredom during the learning process, so that learning can take place efficiently and effectively, restoring students' concentration and enthusiasm for learning and getting ideas for writing in the Schriflicher Ausdruck course. The research questions in this research was how students perceive the implementation of Ice Breaking in the Schriftlicher Ausdruck course. This type of research is explanatory mixed method. The research population was 36 students in the 4th semester of the German language education study program who took the Schriftlicher Ausdruck course and was also used as a sampling. The data collection method was a questionnaire and observation worksheet of ice breaking implementation techniques. Data analysis techniques use descriptive. These results depicted that students looked more active and have high curiosity. The research results showed that as many as 9 students perceived the implementation of ice breaking very well, with a percentage of 25%, 17 students perceived in the good category, with a total percentage of 47.22%, and 10 students perceived quite well with a percentage of 27.78%.